Cross‐sectional study of a United Kingdom cohort of neonatal vein of galen malformation. Issue 4 (4th October 2018) - Lecce, Francesca; Robertson, Fergus; Rennie, Adam; Heuchan, Anne‐Marie; Lister, Paula; Bhate, Sanjay; Bhattacharya, Jo; Brew, Stefan; Kanagarajah, Lakshmi; Kuczynski, Adam; Peters, Mark J.; Ridout, Deborah; et al.
Abstract : Objective: Describe the course and outcomes in a UK national cohort of neonates with vein of Galen malformation identified before 28 days of life. Methods: Neonates with angiographically confirmed vein of Galen malformation presenting to 1 of 2 UK treatment centers (2006–2016) were included; those surviving were invited to participate in neurocognitive assessment. Results in each domain were dichotomized into "good" and "poor" categories. Cross‐sectional and angiographic brain imaging studies were systematically interrogated. Logistic regression was used to explore potential outcome predictors. Results: Of 85 children with neonatal vein of Galen malformation, 51 had survived. Thirty‐four participated in neurocognitive assessment. Outcomes were approximately evenly split between "good" and "poor" categories across all domains, namely, neurological status, general cognition, neuromotor skills, adaptive behavior, and emotional and behavioral development. Important predictors of poor cognitive outcome were initial Bicêtre score ≤ 12 and presence of brain injury, specifically white matter injury, on initial imaging; in multivariate analysis, only Bicêtre score ≤ 12 remained significant. Interpretation: Despite modern supportive and endovascular treatment, more than one‐third of unselected newborns with vein of Galen malformation did not survive. Outcome was good in around half of survivors. The importance of white matter injury suggests that abnormalities of venous as well as arterial circulation are important in the pathophysiology of brain injury. Ann Neurol 2018;84:547–555